Study on Working Conditions of Children in both Organised and Unorganised Industries: Exploring child labor and working conditions in India's manufacturing sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the informal sector, child labour is prevalent in home-based manufacturing operations in most developed countries. Nevertheless, very little is understood about child labour in industrial jobs. The goal of this paper is twofold to understand, on the one hand, if children are more likely to work in home-based work households than other children and, if so, how this affects their abilities and, on the other hand, to outline policy implications for India. This paper builds on ad hoc surveys and a national study conducted in India. This explores the incidence of child labour in such households, the education of the child, and the reasons why children work, their working conditions, and gender problems. For the study of the determinants of child activity status, econometric analysis is applied. Policy effects are spelled out at the end. There can be no more vivid discovery of the soul of a culture than the way it treats its children.